Negotiating FAIRness for Sensitive Interview Transcript Data : Traceability Matrix - User Requirements – Version 1.0 - Mollenhauer, Sabina (Universität Vechta, 2026)
The requirement traceabilty matrix shows all user requirements derived from participatory observation field notes and qualitative interview transcripts analyzed through grounded theory. The column "Data-Sources" references the original field note or interview transcript where the information is located upon which the requirement is based. The data source is matched to a category in the "Categories" column which is part of the grounded theory analysis process. This is followed by the "Req.-ID" column and the "Requirement Statement" column, which together constitute either a functional (FR) or a non-functional (NFR) requirement. Each requirement is matched with one or more use-case specifications defined in the "Use-Case" column: "Metadata", meaning that the requirement applies to metadata implementation; "Publication", meaning that the requirement applies to the persistant publically shared data or its metadata; "De-identification", meaning that the requirement applies to implementation that supports de-identification of data; or "Encryption", meaning that the requirement applies to the implementation of encryption processing of data. The matrix also includes the empty columns "Design-Specification" and "Test-Case-Step", which are relevant in future versions of the matrix in order to track implementation of requirements by matching each with a design implementation and the testing of said implementation in a specific test-case step. Depending on the tracking need of implementation design and testing, these columns may be changed or further columns with regard to these steps may be added in future versions of the traceability matrix.
Keywords: Softwareentwicklung; grounded theory; requirement engineering; requirement traceability; Sozialwissenschaften::300 Sozialwissenschaften, Soziologie::301 Soziologie, Anthropologie; Technik, Medizin, angewandte Wissenschaften; Informatik, Informationswissenschaft, allgemeine Werke